2016
DOI: 10.1002/mnfr.201600493
|View full text |Cite
|
Sign up to set email alerts
|

Zinc supplementation augments TGF‐β1‐dependent regulatory T cell induction

Abstract: Combined zinc and TGF-β1 treatment provoked an increased Treg cell induction due to a triggered intracellular zinc signal, which in association with an increased Smad 2/3 activation leads to a boosted Foxp3 expression and resulting in an ameliorated allogeneic reaction in MLC. Thus, zinc can be used as a favorable additive to elevate the induction of Treg cells in adverse immune reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 79 publications
2
36
0
Order By: Relevance
“…Szuster-Ciesielska et al previously reported that Zn supplementation decreases ethanol- and acetaldehyde-induced activation of liver stellate cells and inhibit liver fibrosis changes though inhibiting TGF-β/Smad signaling [30]. Maywald et al have very recently demonstrated that zinc supplementation increased TGF-β1-dependent regulatory T cell induction in allogeneic reaction due to a triggered intracellular zinc signal, which in association with an increased Smad 2/3 activation [31]. Data from the present study suggested that TGF-β/Smad signaling activation might also occur through this process in NRK-52E cells with HG treatment, and also implicated that ZnT7 protect HG-induced EMT in NRK-52E cells partly by inhibiting TGF-β/Smad signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Szuster-Ciesielska et al previously reported that Zn supplementation decreases ethanol- and acetaldehyde-induced activation of liver stellate cells and inhibit liver fibrosis changes though inhibiting TGF-β/Smad signaling [30]. Maywald et al have very recently demonstrated that zinc supplementation increased TGF-β1-dependent regulatory T cell induction in allogeneic reaction due to a triggered intracellular zinc signal, which in association with an increased Smad 2/3 activation [31]. Data from the present study suggested that TGF-β/Smad signaling activation might also occur through this process in NRK-52E cells with HG treatment, and also implicated that ZnT7 protect HG-induced EMT in NRK-52E cells partly by inhibiting TGF-β/Smad signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, regulatory T cells (Treg) are induced and stabilized in zinc-supplemented mixed lymphocyte culture (MLC), in lymphocytes from patients allergic to pollen [88] and in experimental autoimmune encephalomyelitis (EAE) [89]. Furthermore, zinc enhances the capacity of TGFβ1 to induce Treg cells [90,91]. However, the capacity of zinc to induce Tregs is dependent on the activation status of the cells.…”
Section: Zinc In Inflammationmentioning
confidence: 99%
“…Additionally, regulatory T cells (Treg) are induced and stabilized in zinc-supplemented lymphocyte culture (MLC), in lymphocytes from patients allergic to pollen [83] and in experimental autoimmune encephalomyelitis (EAE) [84]. Furthermore, zinc enhances the capacity of TGFβ1 to induce Treg cells [85,86]. However, the capacity of zinc to induce Tregs is dependent on the activation status of the cells.…”
Section: Zinc Status and Inflammatory Cytokinesmentioning
confidence: 99%